Uji Aplikasi Bakteri Pelarut Fosfat (BPF) dan Amelioran Organik untuk Meningkatkan Pertumbuhan dan Hasil Tanaman Jagung pada Ultisol - Fiqriah Hanum Khumairah; Anggi Jingga; Betty Natalie Fitriatin; Tualar Simarmata (University of Insan Cendekia Mandiri, 2020)
Maize (Zea mays L.) is an important food crop in Indonesia as a source of carbohydrates. The extent of land conversion reduces maize productivity. The experiment aimed to increase the growth and yield of maize in Ultisol which was carried out in the experimental garden of the West Java Horticultural and Various Seed Plant Development Center from October 2017 to March 2018. The Phosphate Solubilizing Bacteria (PSB) and organic ameliorant application test used the factorial randomized block design (RBD) method consisted of two factors. The first factor is PSB and organic ameliorant which consisted of four levels, namely b0 (without the provision of PSB and organic ameliorant), b1 (BP 107 cfu mL-1), b2 (organic ameliorant 5 tons ha-1), and b3 (PSB 107 cfu mL-1 + organic ameliorant 5 tons ha-1) and the second factor is the dosage of SP-36 fertilizer consisted of five levels, namely po (without SP-36 fertilizer), p1 (100% SP-36 fertilizer), p2 (90% SP-36 fertilizer, P3 (80% SP-36 fertilizer), and P4 (70% SP-36 fertilizer). The results showed that the application of PSB (Enterobacter ludwigii + Bulkholderia vietnamiensis + Citrobacter amalonaticus) 107 cfu mL-1 and organic ameliorant dosage of 5 tons ha-1 was able to increase plant height at age 6 Week After Planting (WAP), weight of cob with and without cornhusk, and weight of 100 seeds in the framework of increasing the growth and yield of maize on Ultisols and reduce the use of inorganic P fertilizer to 90%.